Fabrication of Biocompatible, Vibrational Magnetoelastic Materials for Controlling Cellular Adhesion - Holmes, Hal R. (Biosensors (Basel), 2012)
This paper describes the functionalization of magnetoelastic (ME) materials with Parylene-C coating to improve the surface reactivity to cellular response. Previous study has demonstrated that vibrating ME materials were capable of modulating cellular adhesion when activated by an externally applied AC magnetic field. However, since ME materials are not inherently biocompatible, surface modifications are needed for their implementation in biological settings. Here, the long-term stability of the ME material in an aqueous and biological environment is achieved by chemical-vapor deposition of a conformal Parylene-C layer, and further functionalized by methods of oxygen plasma etching and protein adsorption. In vitro cytotoxicity measurement and characterization of the vibrational behavior of the ME materials showed that Parylene-C coatings of 10 µm or greater could prevent hydrolytic degradation without sacrificing the vibrational behavior of the ME material. This work allows for long-term durability and functionality of ME materials in an aqueous and biological environment and makes the potential use of this technology in monitoring and modulating cellular behavior at the surface of implantable devices feasible.